2018
DOI: 10.3389/fmicb.2018.01624
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Iron Transporter SPD_1590 in Streptococcus pneumoniae Contributing to Bacterial Virulence Properties

Abstract: Streptococcus pneumoniae, a Gram-positive human pathogen, has evolved three main transporters for iron acquisition from the host: PiaABC, PiuABC, and PitABC. Our previous study had shown that the mRNA and protein levels of SPD_1590 are significantly upregulated in the ΔpiuA/ΔpiaA/ΔpitA triple mutant, suggesting that SPD_1590 might be a novel iron transporter in S. pneumoniae. In the present study, using spd1590-knockout, -complemented, and -overexpressing strains and the purified SPD_1590 protein, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The genome of Spn does encode several cell membrane-tethered substrate binding proteins (SBPs) coupled to ATP-dependent active transport systems, as classical ATP-binding cassette (ABC) transporters. Three ABC transporters are known or projected to transport Fe III -siderophores, Pit, Pia, Piu, and two additional iron substrate binding proteins may play an accessory role in Fe uptake [20][21][22][23][24]. It is unknown whether Fe II can be imported by S. pneumoniae: although other streptococci encode FeoB, the model serotype 2 Spn strain used here, S. pneumoniae D39, does not.…”
Section: Introductionmentioning
confidence: 99%
“…The genome of Spn does encode several cell membrane-tethered substrate binding proteins (SBPs) coupled to ATP-dependent active transport systems, as classical ATP-binding cassette (ABC) transporters. Three ABC transporters are known or projected to transport Fe III -siderophores, Pit, Pia, Piu, and two additional iron substrate binding proteins may play an accessory role in Fe uptake [20][21][22][23][24]. It is unknown whether Fe II can be imported by S. pneumoniae: although other streptococci encode FeoB, the model serotype 2 Spn strain used here, S. pneumoniae D39, does not.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report implicated an additional Spn protein, Spbhp-22, in iron uptake. In vitro assays showed that Spbhp-22 binds heme, but the mechanism by which this cytoplasmic protein promotes iron or heme intake remains unclear 26 . Since hemoglobin is the primary source of iron during infection, we hypothesized that hemoglobin is vital for pneumococcal pathophysiology.…”
mentioning
confidence: 99%
“…A phosphomimetic mutant, ComE D58E , was constructed by site-directed mutagenesis of comE to exhibit the activity of ComE protein in vitro. Both wild-type ComE and ComE D58E were expressed and purified as described previously (9,33,34). The primers are listed in Table 4 (ComE-F to 16S rRNA-R).…”
Section: Methodsmentioning
confidence: 99%